Rapid GFAP and Iba1 expression changes in the female rat brain following spinal cord injury - Mawj Mandwie; Jordan A Piper; Catherine A Gorrie; Kevin A Keay; Giuseppe Musumeci; Ghaith Al-Badri; Alessandro Castorina (Neural Regeneration Research, 2022)
Evidence suggests that rapid changes to supporting glia may predispose individuals with spinal cord injury (SCI) to such comorbidities. Here, we interrogated the expression of astrocyte- and microglial-specific markers glial fibrillary acidic protein (GFAP) and ionized calcium binding adaptor molecule 1 (Iba1) in the rat brain in the first 24 hours following SCI. Female Sprague-Dawley rats underwent thoracic laminectomy; half of the rats received a mild contusion injury at the level of the T10 vertebral body (SCI group), the other half did not (Sham group). Twenty-four hours post-surgery the amygdala, periaqueductal grey, prefrontal cortex, hypothalamus, lateral thalamus, hippocampus (dorsal and ventral) in rats were collected. GFAP and Iba1 mRNA and protein levels were measured by real-time quantitative polymerase chain reaction and Western blot. In SCI rats, GFAP mRNA and protein expression increased in the amygdala and hypothalamus. In contrast, gene and protein expression decreased in the thalamus and dorsal hippocampus. Interestingly, Iba1 transcripts and proteins were significantly diminished only in the dorsal and ventral hippocampus, where gene expression diminished. These findings demonstrate that as early as 24 hours post-SCI there are region-specific disruptions of GFAP and Iba1 transcript and protein levels in higher brain regions. All procedures were approved by the University of Technology Sydney Institutional Animal Care and Ethics Committee (UTS ACEC13-0069).